Determinants of Expressed Breast Milk Awareness Among Mothers in Siddharthnagar Municipality of Rupandehi District, Nepal - Bhattarai, Sigma; Bhusal, Chet Kant (Journal of Nepal Paediatric Society, 2021)
Introduction: Expressed breast milk is the practice of squeezing breast milk for the purpose of further use. Infant and young child feeding is very important in promoting healthy growth and development, particularly during the first two years of child’s life. The awareness of mothers regarding expressed breast milk has a direct impact on the life of infants and feeding practices. The study aimed to find out possible determinants of awareness regarding expressed breast milk among mothers.Methods: Descriptive cross-sectional study was conducted among 255 mothers from January 2020 to May 2020 by using probability simple random sampling technique. A validated and pre-tested semi-structured interview schedule was used. The data was collected data and analysed.Results: Mean age of mothers was 26 years. 54.1% of the respondents had low awareness regarding expressed breast milk. After adjustment some of the variables such as age of respondents (AOR = 0.03, CI = 0.01 - 0.08, p < 0.001), religion (AOR = 0.36, CI = 0.14 - 0.99, p < 0.001) and educational status of respondents (AOR = 4.40, CI = 1.72 - 11.26, p < 0.001), were significantly associated with level of awareness regarding expressed breast milk. Conclusions: More than half of the mothers had low awareness regarding expressed breast milk. Age of the respondents, religion and educational status were found to be associated factors that influence mother’s awareness regarding expressed breast milk. It is recommended to concerned authority to conduct awareness program regarding expressed breast milk among mothers.